In search of best practice for postpartum depression screening: is once enough?. (November 2016) - Knights, Jayci E.; Salvatore, Michelle L.; Simpkins, Gunda; Hunter, Krystal; Khandelwal, Meena
Abstract: Background: Postpartum depression (PPD) causes significant morbidity in postpartum women and their newborns. Universal screening is mandated in many states despite little information on optimal interval and frequency of screening. Objective: The objective of this study was to determine whether the early Edinburgh Postnatal Depression Scale (EPDS) score (done within 96 h after delivery) is predictive of the late EPDS score (done at outpatient postpartum visit). Study design: This retrospective cohort study selected 256 women delivered at Cooper University Hospital in Camden, NJ in 2013. All patients who presented to the office during the postpartum period completed the EPDS questionnaire, in accordance to our usual practice. The delivery and outpatient records were reviewed for demographic data, EPDS scores and outcomes. Three groups of EPDS scoring were analyzed: <10 (low risk for PPD), 10–13 (borderline risk for PPD), and ≥14 (high risk for PPD). Early and late EPDS scores were compared using Pearson Chi Square test. The relationship between scores was calculated using the Spearman Rho Correlation test. Assuming the EPDS groups would not change, a sample of 200 was needed with 80% power and 5% α-error. Results: EPDS scores remained the same or improved in 92.2% (189/205) of women. The 16 women whose scores worsened were more likely to have had a diagnosis of prior psychiatric illness (50% vs 16.4%, p = 0.003) and/or a diagnosis of fetal anomaly (12.5 vs 1.6%, p = 0.05). An early EPDS score of <10 had a 92.7% probability of maintaining low risk screening (EPDS <10) at a later time. Conclusions: In low risk women, there is good correlation between early and late EPDS scores and so these women may not need to be rescreened. Therefore, we should redirect the limited available resources from screening low risk women multiple times, towards provision of follow-up care for the smaller number of women at highest risk. We propose that " women know your number " (EPDS prior to discharge); and providers re-screen only those women who score positive onPAP10, which stands forP sychiatry history, A nomaly, P reterm delivery, and EPDS score of10 or more.